Peritoneal Dialysis Reduces the Number of Hospitalization Days in Heart Failure Patients Refractory to Diuretics. Issue 1 (January 2014) - Courivaud, Cécile; Kazory, Amir; Crépin, Thomas; Azar, Raymond; Bresson–Vautrin, Catherine; Chalopin, Jean-Marc; Ducloux, Didier
Background: Previous small studies have reported favorable results of peritoneal dialysis (PD) in the setting of chronic refractory heart failure (CRHF). We evaluated the impact of PD in a larger cohort of patients with CHRF where end-stage renal disease was excluded. Methods: All patients who received PD therapy for CRHF between January 1995 and December 2010 in two medical centers in France were included in this retrospective study. Baseline characteristics were compared with clinical parameters during the first year after initiation of PD. Mortality, safety, and sustainability of PD were also analyzed. Results: The 126 patients included had a mean age of 72 ± 11 years and an estimated glomerular filtration rate of 33.5 ± 15.1 mL/min/1.73 m2. Mean time on PD was 16 ± 16.6 months. During the first year, patients with a left ventricular ejection fraction (LVEF) of 30% or less experienced improvement in cardiac function (30% ± 10% vs 20% ± 6%, p < 0.0001). We observed a significant reduction in the number of days of hospitalization for acute decompensated heart failure after PD initiation (3.3 ± 2.6 days/patient–month vs 0.3 ± 0.5 days/patient–month, p < 0.0001). One-year mortality was 42%. Conclusions: In CRHF, PD significantly reduces the number of days of hospitalization for acute heart failure. Improved LVEF may have led to the comparatively good 1-year survival in this cohort.